2016
DOI: 10.1589/jpts.28.3074
|View full text |Cite
|
Sign up to set email alerts
|

The effects on postural control and low back pain according to the types of orthoses in chronic low back pain patients

Abstract: [Purpose] This study investigated how types of lumbosacral orthoses applied to patients with chronic lumbar pain affect postural control and low back pain. [Subjects and Methods] Ten subjects were randomly selected and allocated to each a group wearing soft lumbosacral orthoses and a group wearing rigid lumbosacral orthoses. They wore the lumbosacral orthoses for 4 weeks. Pain index and postural control were measured on the first day of wearing lumbosacral orthoses and 4 weeks later. Pain index was evaluated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…In addition, the extension torque generated by the increased intra-abdominal pressure on this device can reduce muscle activity, tension, and fatigue and reduce the spine load to prevent back pain (Ali et al, 2020;Weiss & Turnbull, 2019). It is supported by previous studies concluding that using a lumbosacral corset could improve posture and lower back pain (Kang et al, 2016).…”
Section: Discussionsupporting
confidence: 76%
“…In addition, the extension torque generated by the increased intra-abdominal pressure on this device can reduce muscle activity, tension, and fatigue and reduce the spine load to prevent back pain (Ali et al, 2020;Weiss & Turnbull, 2019). It is supported by previous studies concluding that using a lumbosacral corset could improve posture and lower back pain (Kang et al, 2016).…”
Section: Discussionsupporting
confidence: 76%
“…Low back pain (LBP) is highly uncomfortable, often chronic sensation in the back below the lower rib cage and above the gluteal fold, often accompanied by leg pain (Kang et al, 2016). According to the National Institutes of Health, about 80% of adults suffer from LBP at some time in their lives.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 27 included studies, 11 studies examined healthy individuals [13,15,16,[38][39][40][41][42][43][44][45], 12 studies examined only LBP patients [37,[46][47][48][49][50][51][52][53][54][55][56], and four studies evaluated both healthy individuals and LBP patients [12,14,17,57] (Table 3). With the exception of one study in which participants had lumbar discopathy [51], most studies examined patients with non-specific LBP.…”
Section: Overview Of Participants' Characteristicsmentioning
confidence: 99%
“…All but three studies [15,41,45] reported the age range of the participants, ranging from 18 to 65 years. Fourteen studies reported pain duration [12,14,17,37,[46][47][48][49][52][53][54][55][56][57] with pain lasting at least >3 months in all studies with the exception of one where patients had LBP with at least 4-week duration [14]. When using 0-10-point pain rating scales, pain intensity varied from 1.5 to 7.7 between studies.…”
Section: Overview Of Participants' Characteristicsmentioning
confidence: 99%